Shared mental models and shared temporal cognitions: contributions to team processes and team effectiveness - Santos, Catarina Marques dos (2017)
The main goal of the thesis is to analyze the effects of shared mental models and shared temporal cognitions on team processes and effectiveness over time. The thesis includes five empirical studies. The findings of the study reported in chapter 2 suggest that relationship conflict mediates the relationship between team mental model similarity at the beginning of the team lifecycle and team effectiveness. Chapter 3 describes a study that reveals that team creativity positively mediates the relationship between shared mental models and team effectiveness; and that intragroup conflict and creativity sequentially mediate the relationship between shared mental models and team effectiveness. Chapter 4 describes a study that suggests that shared temporal cognitions function as a substitute of temporal leadership in reducing temporal conflict. Further, this study provides evidence for the mediating role of temporal conflict between temporal leadership and team performance, and between shared temporal cognitions and team performance. The findings of the study reported in chapter 5 indicate that when accuracy is low, the more similar team members’ temporal mental models are, the less they engage in learning behaviors; and that team adaptation mediates the relationship between team learning and performance. Finally, the findings of the study reported in chapter 6 show that temporal and task mental models are crucial for the translation of team learning behaviors into performance improvement. The thesis contributes to the understanding of teamwork, in particular to the important role of shared mental models and shared temporal cognitions for managing teams in organizational contexts.